Deregulated MicroRNAs Identified in Isolated Glioblastoma Stem Cells: An Overview. Issue 4 (April 2013) - Chua, Pei-Ming; Ma, Hsin-I; Chen, Li-Hsin; Chen, Ming-Teh; Huang, Pin-I; Lin, Shinn-Zong; Chiou, Shih-Hwa
Glioblastoma multiforme (GBM), the most common and aggressive primary brain tumor, is extremely resistant to current treatment paradigms and has a high rate of tumor recurrence. Recent progress in the field of tumor-initiating cells suggests that GBM stem cells (GBMSCs) may be responsible for tumor progression, resistance to treatment, and tumor relapse. Therefore, understanding the biologically significant pathways involved in modulating GBMSC-specific characteristics offers great promise for development of novel therapeutics, which may improve therapeutic efficacy and overcome present drug resistance. In addition, targeting deregulated microRNA (miRNA) has arisen as a new therapeutic strategy in treating malignant gliomas. In GBMSCs, miRNAs regulate a wide variety of tumorigenic processes including cellular proliferation, stemness maintenance, migration/invasion, apoptosis, and tumorigenicity. Nevertheless, the latest progress with GBMSCs and subsequent miRNA profiling is limited by the identification and isolation of GBMSCs. In this review, we thus summarize current markers and known features for isolation as well as the aberrant miRNAs that have been identified in GBM and GBMSCs.